Étudier la perception des services écosystémiques pour appréhender le capital environnemental d’un territoire et ses enjeux de développement, le cas de la péninsule de Karaburun en Turquie - Heval Yildirim; Mélanie Requier-Desjardins; Hélène Rey-Valette (Développement Durable et Territoires)
This paper shows the importance of developing an ecosystem services framework in line with the concept of environmental capital within an operational context of territorial development. A perception study was done in 2014 where 95 local stakeholders in the Karaburun Peninsula were surveyed: farmers, tradesmen, tourists, residents, associations, cooperatives, and municipality. It allows linking the notion of environmental capital to territorial development by identifying the ecosystem services of the peninsula and their potential impact on well-being.